إستراتجيات الخطاب اللغوي في الحديث النبوي الشريف مقاربة لسانية تداولية . كتاب المائة المنتقاة من حديث رسول الله ﷺ أنموذجا: Strategies of Linguistic Discourse in Ḥadīth: A Pragmatic Linguistic Approach Applied on "Kitab Al-Miʾah Al-Muntaqāh" as a Model - حليمة أحمد عمايرة (الدراسات الإسلامية, 2024)
This study explores the prominent discourse strategies in Ḥadīth, focusing on the linguistic mechanisms and their role in conveying the message by the Prophet (peace be upon him). These strategies enabled the text of Ḥadīth to provide pragmatic meanings that shaped thoughts, guided behaviour, and educated addressees. The title of the selected book means “The One Hundred Selected Ḥadīth of the Messenger” and serves as a model. These selected Ḥadīth, when translated to another language, demonstrate the universal and practical applicability of the Prophetic teachings. Ḥadīth, as a legislative linguistic treasure, operates under structural dominants aligned with its discourse strategies. The study adopts modern linguistic approaches, particularly pragmatics, alongside a descriptive statistical method to address its objectives. Pragmatics is employed to uncover the performative capabilities of the linguistic statement, emphasising language as a dynamic tool for communication, action, and societal interaction. The descriptive statistical approach is used to identify the linguistic mechanisms within the structure of the Ḥadīth, linking their external forms to their internal meanings. This approach highlights the universality of the Prophet’s speech, accommodating diverse audiences regardless of their thoughts, beliefs, or environments. The research settled that the Prophet (peace be upon him) effectively employed four primary discourse strategies through various linguistic mechanisms. The statistical analysis of these mechanisms established the success of the Divine message in providing timeless guidance for humanity, adaptable across different eras, locations, and individuals.